2019
DOI: 10.1016/j.compbiomed.2019.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cognitive mental workload via EEG signals and an ensemble deep learning classifier based on denoising autoencoders

Abstract: To estimate the reliability and cognitive states of operator performance in a human-machine collaborative environment, we propose a novel human mental workload (MW) recognizer based on deep learning principles and utilizing the features of the electroencephalogram (EEG). To determine personalized properties in high dimensional EEG indicators, we introduce a feature mapping layer in stacked denoising autoencoder (SDAE) that is capable of preserving the local information in EEG dynamics. The ensemble classifier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Various DCNN architectures with different parameters were selected for this experiment. However, only a few studies in the literature focused on the aggregation of multiple deep CNN models [ 41 , 56 ]. Hence, we were highly motivated to explore the potential of an ensemble model to apply more non-linearities, by connecting the trained weights of the best models obtained from study 2 to improve the final performance.…”
Section: Resultsmentioning
confidence: 99%
“…Various DCNN architectures with different parameters were selected for this experiment. However, only a few studies in the literature focused on the aggregation of multiple deep CNN models [ 41 , 56 ]. Hence, we were highly motivated to explore the potential of an ensemble model to apply more non-linearities, by connecting the trained weights of the best models obtained from study 2 to improve the final performance.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the controllers dealt with realistic ATM tasks in ecological settings. Thirdly, studies employing multimodal and machine-learning approaches did not consider the importance and meaning of the selected neurophysiological features 58,[61][62][63] . In fact, they usually made blind selections from a very large set of features in order to achieve high-classification accuracy.…”
Section: Neurophysiology Of Stressmentioning
confidence: 99%
“…Therefore, the application of Machine Learning has been considered the solution for classifying the workload and overcoming these issues typical of real applications. The preliminary analysis of the works carried out so far in this context has shown that it is possible to discriminate with acceptable accuracy only two levels of workload [6], [18], [22], [24], [25], [27]- [29], [33], [36]- [39], [42], [45], [46], [58], even though, above all in view of a practical application of the workload measurement, it is necessary to establish at least the value of two thresholds to define the underload and the overload state. The most frequently employed features are the spectral ones, because they can be calculated with a high temporal resolution (up to one second) and allow to monitor brain activity in a quantitative manner without temporal triggers.…”
Section: Discussionmentioning
confidence: 99%
“…Once defined a meaningful set of features, it is necessary to choose a model to define the workload level. In the literature innumerable algorithms, essentially of a supervised nature, have been used to define the workload level of a subject starting from his brain signals, belonging to both the so-called Shallow learning and deep Learning domains [45], [46]. In all cases the efficiency of such algorithms is usually presented in terms of accuracy.…”
Section: Machine Learning To Get Back Out-of-the-labmentioning
confidence: 99%